Internalisasi Nilai-Nilai Pancasila sebagai Dasar Penanaman Karakter Siswa MI Islamiyah Muhammadiyah Walikukun - Darmanto (Prodi Pendidikan Guru Sekolah Dasar, 2025)
The purpose of this study is to comprehend and describe the internalization process of Pancasila as the foundation for student character at MI Islamiyah Muhammadiyah Walikukun. This type of research is qualitative research using a kasus study approach. Data collection techniques include documentation, observation, and wawancara. Wawancara mendalam is performed for the madrasah head, curriculum coordinator, school teacher, and wali murid. According to this study, internalization of Pancasila as a foundation for character development occurs through three stages: The transformation of nilai is carried out through apel pagi and kepanduan activities that are participated in by all students; the nilai transaction is carried out through learning activities both inside and outside of schools, market day activities, and prakarya; the internalization phase is carried out by creating two communication channels, either with students or with parents.